Solutions of Some Integrals in Hypergeometric Functions and their Generalization in Double Series Identities - Usha Gill; Ranjana Shrivastava; Kaleem A. Quraishi; Z. A. Taqvi (International Journal of Mathematics And its Applications, 2015)
In this paper, we obtain solutions of some integrals in the form of hypergeometric functions. Further, we generalize these integrals in the form of double series identities involving bounded sequences. We also derive hypergeometric forms of these identities involving Gaussian hypergeometric function, Srivastava-Daoust double hypergeometric function and Kampe de Feriet double hypergeometric function.